THE ROLE OF LOUROS AND ARACHTHOS RIVERS IN THE DEVELOPMENT OF SEDIMENTS OF THE ARTA’S PLAIN WITH THE CONTRIBUTION OF GEOCHEMICAL PARAMETERS - Βρυνιώτης Δ.; Παπαδοπούλου Κ. (Bulletin of the Geological Society of Greece, 2004)
The investigated region, which consists of a flat part to the north of Amvrakikos gulf, has high values with respect to Ni and Cr in alluvial soil. Specifically, within the area bounded by Rodia’s lagoon, Arta’s and Arachthos delta there are very high values of Ni and Cr with spatial correlation of the three higher classes of nickel (152-254 ppm) and chromium (111-186 ppm). In the surrounding area there are also elevated values of Ni and Cr. These high values of Ni and Cr are derived from the weathered ultra-basic materials, transported by Arachthos river from the northern part of the greater region, where the Pindos ophiolite complex is developed. Whereas, Louros river does not carry a load of ultra-basic materials. The conclusions of this investigation are: a) The most recent sediments of the flat part within Rodia’s lagoon, Arta’s and Arachthos delta are exclusive deposits of Arachthos river after its separation from Louros, b) In the surrounding area, and especially to the West there are older sediments deposited by Arachthos and Louros before their break-up, and c) The contribution of Louros in the sediments of the flat part is minor